(untitled) (International Journal of Engineering and Computer Science, 2014)
With the advances in information and communication technology, increase in school enrolments and the need for more reliability in students’ assessment, Computer-Based Testing (CBT) is recently gaining more popularity as a means of administering tests in educational institutions and corporate organisations. This paper reports the development of a computer-based test platform for Centre of Entrepreneurship Development and Vocational Studies (CEDVS) of The Federal Polytechnic, Ado-Ekiti, Nigeria. A free and open source software (FOSS) called MOODLE was used to develop the platform. The platform was test run to administer tests to students offering Entrepreneurial Courses in the Polytechnic. Out of 202 students tested, 89% preferred CBT to paper-based tests, 92% agreed that the platform was interactive and easy to use while 12% believed that the use of CBT will make test taking difficult.